Robotic Full Lobe Hepatectomy With Natural Orifice Extraction: Case Series Describing the Novel Technique of Robotic Major Hepatectomy and Transvaginal Specimen Extraction. Issue 1 (16th March 2021) - Glorioso, Jaime M.; Nguyen, Michelle C.; Long, Jane; Jackson, Kyle; Philosophe, Ralph; Wethington, Stephanie L.; Philosophe, Benjamin
Abstract : Mini-abstract: A minimally invasive approach to partial hepatectomy with transvaginal specimen extraction is safe and feasible with the potential to improve the cosmetic outcome, minimize postoperative narcotic utilization, and shorten hospital length of stay. This series describes the initial experience using this novel technique.